Biofouling of membranes in microbial electrochemical technologies: Causes, characterization methods and mitigation strategies. (May 2019) - Koók, László; Bakonyi, Péter; Harnisch, Falk; Kretzschmar, Jörg; Chae, Kyu-Jung; Zhen, Guangyin; Kumar, Gopalakrishnan; Rózsenberszki, Tamás; Tóth, Gábor; Nemestóthy, Nándor; Bélafi-Bakó, Katalin
Graphical abstract: Highlights: Membrane separator properties in MET from biofouling viewpoint are assessed. Methods for membrane biofouling characterization are discussed. Experiences with various membrane separators used in MET are analyzed. Status and challenges for membrane biofouling in MET are presented. Abstract: The scope of the review is to discuss the current state of knowledge and lessons learned on biofouling of membrane separators being used for microbial electrochemical technologies (MET). It is illustrated what crucial membrane features have to be considered and how these affect the MET performance, paying particular attention to membrane biofouling. The complexity of the phenomena was demonstrated and thereby, it is shown that membrane qualities related to its surface and inherent material features significantly influence (and can be influenced by) the biofouling process. Applicable methods for assessment of membrane biofouling are highlighted, followed by the detailed literature evaluation. Finally, an outlook on e.g. possible mitigation strategies for membrane biofouling in MET is provided.